Voices from Bears Ears : seeking common ground on sacred land - Robinson, Rebecca, 1984- (The University of Arizona Press, in association with George F. Thompson Publishing, 2018)
"This book captures the passion and history embedded in local conversations about Utah's Bears Ears National Monument"--Provided by publisher.